Synthesis of Bio-diesel and Bio-lubricant by transesterification of vegetable oil with lower and higher alcohols over heteropolyacids supported by clay (K-10) - Bokade, Vijay V.; Yadav, G. D. (Process Safety and Environmental Protection, 2007)
{The use of different lower and higher alcohols viz; methanol, ethanol, n-propanol and n-octanol, for the synthesis of methyl, ethyl, propyl and octyl fatty acid esters by transesterification of vegetable oil (triglycerides) with respective alcohols also known as `Bio-diesel' and `Biolubricants' was studied in detail. The reactions were carried out in a batch process. The activity with different supports like clay (K-10), activated carbon, ZSM-5, H-beta and TS-1 were compared. The superacids (heteropolyacids, HPA) viz; Dodeca-Tungstophosphoric acid [
Theoretical Chemistry Symposium 2006 (TCS 2006), Bharathidasan Univ, Trichy, INDIA, DEC 11-13, 2006
Keywords: coprecipitation; lithium aluminate; Microemulsion; Nanoparticles; sol-gel; Surfactants

Synthesis of pharmaceutical intermediates by toluene benzylation over heteropoly acids on different support - Bokade, Vijay V.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{Selective formation of pharmaceutical intermediates like diphenylmethane, dimethyl-diphenylmethane, benzyl toluene and benzoic acid by liquid phase, toluene benzylation with benzyl chloride as a benzylating agent, was systematically studied over plane clay (K-10, montmorillonite), plane H-Beta, plane MFI structured titanosilicate (TS-1) and heteropoly acids [
International Conference on Nano Science and Technology (ICONSAT 2006), New Delhi, INDIA, MAR 16-18, 2006
Keywords: heteroassembly; nanoplates; polyfunctional capping agents; shape selective synthesis of gold-silver nanostructures; surface confinement